فن الخط العربي: دراسة تاريخية، تقنية وجمالية - الحناوي، حسام فؤاد سعيد Alhennawi, Hossam Fouad Said (جامعة العلوم التطبيقية الخاصة - عمادة البحث العلمي والدراسات العليا, 2017)
يتناول هذا البحث الخط العربي، جماليته وخصائصه الفنية وأهميته في الفنون الإسلامية. قال تعالى: [ن والقلم وما يسطرون] سورة القلم من هذا المنطلق جاء اهتمام الخطاط المسلم بالكتابة والعناية بالخط لأن الدافع قبل كل شيء هو دافع ديني لما تتميز به اللغة العربية من خصائص وتحتفظ به من قدسية في نفوس المسلمين. "ومن هنا أخذ هذا الفن مكانته بين الفنون جميعاً، ونجد الخطاطين ينشطون في إبداع مختلف اللوحات الخطية ويتفننون في تصويرها على مختلف الآثار". وهكذا بدأت تظهر بين آونه وأخرى نماذج متعددة وجديدة من الخطوط التي أبدع صانعوها في رسومها وزخرفتها فكان الخط النسخي وكان الخط الكوفي وخط الثلث وغير ذلك، وقد شكلت هذه المرحلة التي مر بها الخط العربي، مرحلة نهوض حضاري حيث رافقها نوع من الاهتمام البالغ والتأنق الملحوظ في رسم الخط وإيصاله إلى أذواق الناس، فخرج من إطار الكتابة التقليدية إلى أغراض جمالية وترف ذوقي. الحالة التي مر بها اغلب الفنون الأخرى، ألا انه بلغ في الخط العربي وفنونه مرحلة بعيدة، تمكن فيها الخطاط العربي إلى وضع أشكال جديدة للكتابة العربية ومن أبرزها الكتابة على هيئة صور ورسوم باعتبارها حلية للخط والزخرفة وليس غرضا مقصوداً للكتابة، مع المحافظة على روح المعنى والاستعانة بمعطيات التراث. ومن هذا المنظور انجز الفنان المسلم أعظم لوحاته الفنية باستخدامه الحرف العربي وقد ساعده في ذلك قابلية الحرف للتشكيل: المد والاستدارة والبسط والصعود والهبوط واللين. يهدف هذا البحث إلى إلقاء الضوء على الخط العربي وخصائصه الفنية والجمالية التي جعلت منه عنصراً زخرفياً مهما في الفنون الإسلامية.
This paper is inspired by Arabic calligraphy, aesthetics, technical characteristics and its importance in Islamic Art. In the Name of ALLAH: (Nun. By the pen and what they inscribe,) (Alqalam) Based on this fact, Muslim calligrapher became interested in the art of calligraphy with a great focus on script Styles, it is significant to mention that religious motivation and the characteristics of the Arabic language had its impact and retained its sanctity in the hearts of Muslims. Hence, I Calligraphy, is the most revered form of artistic expression in the Islamic world, for it was through the act of writing that the holly book “Quran”, Consequently, Calligraphy became the most recognizable and ubiquitous symbol of Islam art. Thus calligraphers are very active in order to create different types of calligraphy, Most of the Islamic ruins that survive today are witness to this art. Thus it began to appear, from time to time, that Arabic calligraphy is a fascinating art form giving rise to expressions that combine spiritual meaning with aesthetic beauty. Numerous Styles of script have been developed over time each with a variety of expressions and yielding different compositions. These include several new models of calligraphy such as, A1 Nasikh, Kufic and A1 Thuluth... etc. It is remarkable that Islamic calligraphy is asegnificant of the advancement of Islamic civilization and was accompanied by such type from the utmost attention in calligraphy as a unique and deliver this kind of Art to people. Stepped out of the traditional framework of writing to focus on aesthetic and luxury purposes. The genius of Islamic calligraphy lies not only in the endless creativity and versatility, but also in the balance Struck by calligraphers between transmitting a text and expressing its meaning through a formal aesthetic code. Focusing on form and illustration as well as ornaments as part of a decorative designs. This Study aims to focus on Arabic calligraphy, its technical characteristics and aesthetics which is considered one of the most important forms of art
Keywords: الخط العربي -- الفن الإسلامي -- الخزف الإسلامي